2020
DOI: 10.1093/texcom/tgaa006
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Prestimulus Oscillations in Developmental Dyslexia Support an Underlying Attention Shifting Deficit

Abstract: Abstract Developmental dyslexia (DD) impairs reading and writing acquisition in 5–10% of children, compromising schooling, academic success, and everyday adult life. DD associates with reduced phonological skills, evident from a reduced auditory mismatch negativity (MMN) in the electroencephalogram (EEG). It was argued that such phonological deficits are secondary to an underlying deficit in the shifting of attention to upcoming speech sounds. Here, we tested whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…A key finding of our study is that the AVG group was significantly faster than the NAVG group at localising an auditory target (Castel et al, 2005;Dye, Green, & Bavelier, 2009), but only when the cue was presented to the opposite side of the target (invalid condition). First, this result is in line with research suggesting that AVG players have faster stimulus-response mappings that lead to the rapid execution of responses to both visual and auditory targets in the environment (Castel et al, 2005;Dye et al, 2009;Green & Bavelier, 2003;Meyer & Schaadt, 2020). Second, it suggests that the AVG players are better at disengaging their auditory attention from the invalid cue location and are more efficient at reallocating attentional resources to a previously uncued position regardless of SOAs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A key finding of our study is that the AVG group was significantly faster than the NAVG group at localising an auditory target (Castel et al, 2005;Dye, Green, & Bavelier, 2009), but only when the cue was presented to the opposite side of the target (invalid condition). First, this result is in line with research suggesting that AVG players have faster stimulus-response mappings that lead to the rapid execution of responses to both visual and auditory targets in the environment (Castel et al, 2005;Dye et al, 2009;Green & Bavelier, 2003;Meyer & Schaadt, 2020). Second, it suggests that the AVG players are better at disengaging their auditory attention from the invalid cue location and are more efficient at reallocating attentional resources to a previously uncued position regardless of SOAs.…”
Section: Discussionsupporting
confidence: 85%
“…In particular, they suggest that auditory attention disengagement may play a fundamental role in reading through both phoneme discrimination -necessary for phonological decoding through graphene-to-phoneme mapping -and phonological short-term memory (Facoetti, Lorusso, Cattaneo, Galli, & Molteni, 2005;Ruffino, Gori, Boccardi, Molteni, & Facoetti, 2014). Supporting this hypothesis, studies have shown a significant link between auditory attentional shifting skills and both phonological processing and reading, using several tasks involving the rapid serial presentation of auditory stimuli, such as attentional blink tasks (Lallier, Donnadieu, Berger, & Valdois, 2010), auditory stream segregation tasks (Lallier et al, 2009;Lallier, Tainturier, et al, 2010), auditory spatial attentional orienting tasks Facoetti et al, 2005Facoetti et al, , 2010, and audio-visual oddball tasks (Meyer & Schaadt, 2020). If reading-related attentional benefits for AVG players are observed in the auditory modality (Green, Pouget, & Bavelier, 2010), this would suggest that the previously reported association between playing AVGs and the enhancement of reading skills is probably not solely mediated by a boost of visual attention skills.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, increased theta ITC has been previously associated with an attentional shift in participants hearing their own name (Tamura et al, 2015), and some evidence points toward impaired auditory attentional interference control in dyslexic readers (Gabay et al, 2020), which may render them more susceptible to involuntary attention switching. This differs from recent reports of decreased attentional shifting to upcoming stimuli in dyslexic children in an audiovisual oddball paradigm (Meyer & Schaadt, 2020). However, this study investigated pre-stimulus alpha ITC, and required children to direct their attention toward the visual speech stimuli which preceded the auditory onset, thus highlighting impairments in endogenous attentional control, rather than involuntary attention switches.…”
Section: Discussionmentioning
confidence: 69%
“…Two very recent studies have shown moderate to strong effects of a rapid automatized naming (RAN) training on reading [40,41]. In addition, some researchers suggest that this deficit in phonological processing is the consequence of a more fundamental deficit in the perceptual and/or attentional processing of auditory information [42][43][44][45][46][47][48][49]. For example, allophonic perception of speech sounds in subphonemic units can lead to poor discrimination of acoustic differences, a perceptual deficit in phoneme categorization and consequently a deficit in phonological processing.…”
Section: Background {6a}mentioning
confidence: 99%